Aplikasi Smartphone sebagai Sarana Promosi Kesehatan Kanker dengan Terapi Radiasi - Hana Dodik Pramiasti; Agung Waluyo; Yati Afiyanti (Journal of Telenursing (JOTING), 2022)
This study aims to determine the benefits of using smartphone applications in the health sector in increasing the knowledge of patients or survivors about cancer health, prevention, early detection and screening of cancer, especially treatment with radiation modalities. The method used is PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) on several electronic databases through screening titles about cancer education or health promotion with radiation therapy. The results showed that many smartphone applications in the field of cancer services were used in patients receiving radiation therapy. This application is very useful for cancer patients during treatment and for post-therapy survivors. The m-Health application is also able to increase patient knowledge about cancer and can encourage changes in healthy living behavior. In conclusion, health promotion and intervention through smartphone applications can have a positive impact on improving health quality, both physically and psychologically, socially, increasing health literacy and being economically more cost-effective. Keywords: Applications, Education, Cancer, Radiotherapy, Smartphone